DETERMINATION OF FIRM VALUE THROUGH GOOD CORPORATE GOVERNANCE, CAPITAL STRUCTURE, AND FIRM SIZE: A STUDY OF IICD AWARDEES 2021–2024 - Rara Wiritanaya; Rohmawati Kusumaningtias; Suhaily Hasnan (Politeknik Negeri Ambon, 2026)
Introduction: This study examines the effect of Good Corporate Governance, capital structure, and firm size on firm value in companies receiving the Indonesia Institute for Corporate Directorship Corporate Governance Award during 2021–2024.Methods: This research uses a quantitative approach with secondary data from annual reports and financial statements of 17 awardee companies selected through purposive sampling. Data are analyzed using multiple linear regression. Firm value is measured by Tobin’s Q, Good Corporate Governance by the board of directors, independent commissioners, audit committee, and board meeting frequency, capital structure by the debt to equity ratio, and firm size by the natural logarithm of total assets.Results: The results show that the board of directors and capital structure have a positive and significant effect on firm value, while independent commissioners, audit committee, and board meeting frequency are not significant. Firm size has a significant negative effect on firm value. All variables jointly affect firm value.Conclusion and suggestion: The findings indicate that effective governance mechanisms and optimal capital structure are essential for enhancing firm value. Keywords: Capital Structure, Company Size, Company Value, Good Corporate Governance, Tobin’s Q